Greater Paris: A Plan for a Global City - Lise Bourdeau-Lepage (European Regional Science Association (ERSA), 2014)
Over the last decade or so, the debate on the planning and development of the Paris (Île-de-France) region has revolved around two little words: "Grand Paris", or Greater Paris. Despite existing political and scientific controversies surrounding the future of the capital region, three major issues, different but interdependent in nature, have emerged. The first is the economic development of Paris and its place on the world stage (section 1); the second is socio-spatial justice and quality of life in the region (Section 2); and the third is governance (Section 3). These three issues, in our opinion, are key to understanding the processes currently under way in the Île-de-France region in connection with the concept of a Greater Paris. The aim of this paper is to stimulate scientific discussion by exploring each of these issues on the basis of the key stylized facts and the rationales of the various stakeholders.
Keywords: R11; R12; R20; R28; R50; R53; R58; 330